Nitrogen-incorporated ultrananocrystalline diamond/multilayer graphene composite carbon films: Synthesis and electrochemical performances. (10th December 2017) - Peng, Xiaolan; Yuan, Wen; Zou, Jiaxiu; Wang, Bing; Hu, Wenyuan; Xiong, Ying
Graphical abstract: Highlights: A novel N-UNCD/MLG composite carbon film was deposited using diethylamine as the sole carbon and nitrogen sources. The N-UNCD/MLG composite films exhibited large electrical double layer capacitance and high cyclic stability. Low detection limit for Ag + could be obtained in the N-UNCD/MLG composite films. Abstract: Novel nitrogen-incorporated ultrananocrystalline diamond/multilayer graphene (N-UNCD/MLG) composite carbon films were deposited on silicon substrates via a microwave plasma chemical vapor deposition (MPCVD) method, in which diethylamine was utilized as the sole carbon and nitrogen sources. In the composite films, MLGs are grown vertically on substrate surface and interlaced together to build a porous nest-like morphology. Many ultra-small N-UNCDs are dispersed uniformly inside the 'nest'. Using [Fe(CN)6 ] 3−/4− as redox probe, the electrochemical activity of N-UNCD/MLG films is investigated and the real electrochemical active area is also estimated. The N-UNCD/MLG films process large electrochemical double layer capacitance (EDLC) of 327.4 μF cm −2 for cyclic voltammetry (CV) measurement and of 306.5 μF cm −2 for glavanostatic charge-discharge (GCD) measurement. After 10000 charge/discharge cycles, the reduction of EDLC is only about 10.3%. For the electrochemical detection of Ag +, this film presents high sensitivity (69 nA ppb −1 ) and low detection limit (∼0.46 ppb). Therefore, the N-UNCD/MLG films with large EDLC and robust cyclic stability would be a new class of carbon-based electrodes for the application in electrochemical energy storage and/or electrochemical sensing.